99mTc‐human serum albumin nanocolloids: particle sizing and radioactivity distribution. (21st July 2015) - Persico, Marco G.; Lodola, Lorenzo; Buroni, Federica E.; Morandotti, Marco; Pallavicini, Piersandro; Aprile, Carlo
<x xml:space="preserve">Abstract</x> Several parameters affect the biodistribution of administered nanocolloids (NC) for Sentinel Lymph Node (SLN) detection: particle size distribution, number of Tc atoms per particle and specific activity (SA). Relatively few data are available with frequently conflicting results. 99mTc‐NC‐human serum albumin (HSA) Nanocoll®, Nanoalbumon® and Nanotop® were analysed for particles' dimensional and radioactivity distribution, and a mathematical model was elaborated to estimate the number of particles involved. Commercially available kits were reconstituted at maximal SA of 11 MBq/µg HSA. Particles size distribution was evaluated by Dynamic Light Scattering. These data were related to the radioactivity distribution analysis passing labelled NC through three polycarbonate filters (15‐30‐50‐nm pore size) under vacuum. Highest radioactivity was carried by 30–50 nm particles. The smallest ones, even though most numerous, carried only the 10% of 99mTc atoms. Nanocoll and Nanotop are not significantly different, while Nanoalbumon is characterized by largest particles (>30 nm) that carried the most of radioactivity (80%). Smallest particles could saturate the clearing capacity of macrophages; therefore, if the tracer is used for SLN detection, more node tiers could be visualized, reducing accuracy of SLN mapping. Manufacturers could implement technical leaflets with particle size distribution and could improve the labelling protocol to provide clinicians useful information.